Primary mediastinal seminoma with florid follicular lymphoid hyperplasia: a case report and review of the literature - Charlotte Holmes; Peh Sun Loo; Sion Barnard (BMC, 2021)
Abstract Background First described in 1955 Primary mediastinal seminomas are rare. Only 1-4% of mediastinal tumours are germ cell tumors; majority of which are teratomas. They typically present in men aged between 20 and 40 years. Very few cases are reported in the literature. Florid follicular lymphoid hyperplasia can obscure the malignant cells and is a rarer finding still. We present a rare case of a 48 year old man with a primary mediastinal seminoma with florid follicular lymphoid hyperplasia; found following excision of a clinically presumed thymoma. Case presentation A 48 year old man was referred for excision of a thymic mass. The presumed diagnosis was a thymoma; following preoperative investigations. The mass was incidentally found on a radiological imaging. However, the patient did report mid-sternal discomfort on lying flat and breathlessness. The patient underwent a thymectomy via a partial median sternotomy with good recovery. Histological assessment was that the mass was in fact a primary mediastinal seminoma with florid follicular lymphoid hyperplasia. A primary testicular malignancy was excluded and the patient required no further oncological treatment. Conclusions Only 11 cases have previously been reported of primary mediastinal seminoma with florid follicular lymphoid hyperplasia. Although rare, a primary mediastinal seminoma should be considered as a differential diagnosis for presentations with a thymic mass. Tumour markers can be helpful, however are only positive in third of cases. Ultrasound imaging of the gonads is essential to exclude a primary gonadal lesion. Pure seminomas are radiotherapy and chemotherapy sensitive however the mainstay treatment of primary mediastinal seminomas remains surgical excision. Radiotherapy is reserved postoperatively for incomplete surgical margins.